Earnings Management, Value Relevance Of Earnings and Book Value of Equity - Imam Subekti (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2010)
Previous studies examining relationship between earnings management and value relevance of accounting information show that earnings management decrease value relevance of accounting information. Generally, the studies apply accruals earnings management. In contrast, the present study applies integrated earnings management proxies i.e. real and accruals earnings manage-ment. Real earnings management proxies are measured by abnormal cash flow of operation, ab-normal production cost, and abnormal discretionary expenses. On the contrary, accruals earn-ings management proxies are measured by short and long term discretionary accruals matched performance.The objective of the present study is to investigate the effect of the earnings management proxies integrated by factor analysis on value relevance of earnings and book value of equity. Re-sults of the present study show earnings and book value of equity are relevant in measuring firm market value, and integrated earnings management decrease the value relevance of earnings and book value of equity. Keyword: integrated earnings management, value relevance of earnings and book value of equity